Ecological issues - Pierce, A.R.; Shanley, P. (Routledge, 2002)
To manage non-timber forest products (NTFPs) properly, it is imperative to have a basic understanding of the biology and ecology of the target species, the site capabilities of the forest under management and the response of the target species o harvesting and other human and natural disturbances. This chapter explores ecological issues relating to NTFP harvest, including knowledge of species harvested, harvest impacts and the importance of trained harvesters.